ANGIOTENSIN CONVERTING ENZYME INHIBITORS IN ACUTE MYOCARDIAL INFARCTION: WHEN TO START THERAPY AND WHICH DRUG TO USE? - S. Y. Martsevich; S. N. Tolpygina (Столичная издательская компания, 2015)
Data of studies devoted to application of angiotensin converting enzyme (ACE) inhibitors in acute myocardial infarction are reviewed. The reasons of ambiguous results are discussed. A point of view that different ACE inhibitors may have the various efficacy and safety in patients with acute myocardial infarction is suggested.